2019
DOI: 10.1002/mgg3.775
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic polymorphism of PC‐1 gene (rs1044498 Lys121Gln) with insulin‐resistant type 2 diabetes mellitus in Punjabi Population of Pakistan

Abstract: Background Insulin resistance (IR), known to reduce the response to insulin action, develops with obesity leading to type 2 diabetes mellitus (T2DM). The PC‐1 gene has been associated with dyslipidemia, polycystic ovarian disease and T2DM in different regions of the world. The objective of the present study was to investigate the genetic association of PC‐1 rs1044498 polymorphism with insulin resistance in type 2 diabetes in the Punjabi population of Pakistan. Methods This study was carried out on 161 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…Research done in China also revealed that T2DM or any of the characteristics of the metabolic syndrome have no correlation with PC-1 K121Q polymorphotype distribution (Daoming et al, 2006). The present findings differed from those of Abdo Albegali et al (2019), who found a correlation between PC-1 and the incidence of type 2 diabetes in the Punjabi population of Pakistan. While other studies have showed no link of this allele with illness risk (Rasmussen et al, 2000), prior research has demonstrated a correlation between the Q allele of PC1 (rs1044498) and insulin resistance (Gu et al, 2000).…”
Section: Discussioncontrasting
confidence: 94%
“…Research done in China also revealed that T2DM or any of the characteristics of the metabolic syndrome have no correlation with PC-1 K121Q polymorphotype distribution (Daoming et al, 2006). The present findings differed from those of Abdo Albegali et al (2019), who found a correlation between PC-1 and the incidence of type 2 diabetes in the Punjabi population of Pakistan. While other studies have showed no link of this allele with illness risk (Rasmussen et al, 2000), prior research has demonstrated a correlation between the Q allele of PC1 (rs1044498) and insulin resistance (Gu et al, 2000).…”
Section: Discussioncontrasting
confidence: 94%
“…It was suggested that the incremental increase in PC in liver-derived microsomes in vitro or the extra PC level in the membrane restrains calcium homeostasis in organelles regulated by the calcium transport activity of sarcoendoplasmic reticulum Ca 2+ -ATPase (SERCA), which results in protein misfolding and endoplasmic reticulum (ER) stress, and nally stimulates insulin resistance. 96,97 HQLYD validly reduced the contents of PC(18:1(9Z)/15:0), PC(15:0/20:3(8Z,11Z, 14Z)) and PE(14:0/24:1(15Z)) by regulating glycerophospholipid metabolism and glycosylphosphatidylinositol(GPI)-anchor biosynthesis. D-glucose exists in the blood, spinal uid and lymph of animals, and is used as a nutrient for diuretic, detoxication and cardiotonic.…”
Section: Discussionmentioning
confidence: 99%
“…Journal of Diabetes Research [37], South Africans of mixed-ancestry [38], Chinese [39,40], Americans, Europeans, Africans [41], Asians [42], and Zanjans [43], but others have found no link in Pakistani Punjabis [44], Malaysians [45], Lebanese and Tunisians [46], Chinese [47,48], and Danish Caucasians [49]. To understand its specific molecular significance in insulin resistance, more research with bigger sample sizes is required.…”
Section: Negative Regulation Of Irmentioning
confidence: 99%